Indução dos resultados da avaliação externa de larga escala na formação continuada de uma rede municipal de ensino - Melo, Teresinha Aparecida Bernardineli de Oliveira (2023)
The results of large-scale external evaluations and the indices associated with them have influenced both networks and individual schools, and the literature on the subject has denounced the adoption of actions aimed at raising indicators. This dissertation is the result of research contextualized in the debate on the consequences of external evaluation policies. on the consequences of large-scale external evaluation policies on the delimitation of proposals and the actions of education networks. examine how the results of large-scale external assessments induce continuing education for teachers and school managers carried out by the Municipal Department of Education of Limeira, whose improvement in results was observed between 2015 and 2019 and widely credited by the network's management specific actions, with emphasis on investment in the practice of continuing education training of education professionals. Methodologically, we used document research to characterize, describe and analyze the network's training actions related to large-scale external evaluation policies. as a source of data the archives of the Municipal Department of Education referring to training from 2013 to 2021. Our data reveals, among other aspects, the adoption of actions linked to the logic of the search for results, with the induction by the network's training team of activities aligned with the performance of the students in the tests, an aspect that indicates the use of the training to help improve results in large scale external assessments.